THE EFECTS OF PARENTING STYLES ON INDEPENDENCE OF CHILDREN IN KINDERGARTEN, GORONTALO - Pupung Puspa Ardini; Afika Lamadi; Setyo Utoyo (Universitas Muhammadiyah Ponorogo, 2019)
The problem in this study was that there were still 30% of children who were still dependent on others, especially parents and did not want to try when doing something because they usually got helps, especially in Gorontalo. The research aimed to know the effects of parenting styles of parents on the independence of early childhood. This study was an expost facto quantitative research with intact group comperation design. This study was conducted at TK Negeri Pembina Ki Hajar Dewantoro Kota Selatan Kota Gorontalo. The objects of this study were parenting and children's independence. Data about parenting styles of parents were collected through a questionnaire. Meanwhile, data on children's independence were collected through observation using a checklist assessment table. From the results of the study obtained by using person correlation with the value of r = 0.702 and ttotal value = 0.468 or rxy ttotal, there was an effect between parenting styles of parents with the independence of early childhood and data analysis techniques used t-test obtained t-test value = 0.53 and ttable = 1.73., in other words, tcount ≤ ttable or p-value alpha so that Ho was rejected and Ha was accepted. Therefore, there was a significant effect between parenting styles of parents on the independence of children in group A TK Pembina Ki Hajar Dewantoro Selatan City Gorontalo City.